Networks and networking: the public administration agendas - O'Tool, Laurence J., Jr. (2015)
Published in 1997, the article Treating Networks Seriously: Practical and Research-Based Agendas in Public Administration outlined the importance of networks for the field of public administration and suggested a series of research agendas that should be pursued. That argument has received substantial attention in the years since. Research on networks and networking has made substantial progress, particularly on some questions the descriptive agenda, for instance, and some aspects of the practical agenda. However, considerable work remains to be done. More needs to be known about the ways in which networks and networking behavior can shape performance and affect the most salient values in our governance systems; better empirical theory is also needed in this regard. Such further developments would be of immense value to the practice of public administration. The world of public administration has for some time been treating networks seriously, but the work is far from complete.- Reproduced.
Keywords: Public administration